(untitled) (Journal of Medicine, 2017)
Background and Purpose: Diabetes and ischemic stroke are common diseases that frequently occurring together. Several studies have shown that people with diabetes have approximately twice the risk of ischemic stroke compared with those without diabetes. Although diabetes is a strong risk factor for ischemic stroke, it is still unclear whether risk factors, neuroimaging findings and hospital outcome are different in diabetic and nondiabetic patients. The aim of the present study was to evaluate cerebrovascular risk factor prevalence, neuroimaging findings and hospital outcome in patients between diabetic and non-diabetic of ischaemic stroke. Methods: We conducted a prospective study of 380 consecutive patients with cerebral infarction admitted into Rangpur Medical College Hospital over a 18-month period. With the use of a simple identical data sheet, we recorded the demographics, cardiovascular risk factors, neuroimaging findings and outcome in ischemic stroke patients with and without diabetes. Results: Overall, diabetes was present in 76 patients (20%). Diabetic patients, compared with those without diabetes, were younger (p=.034) and they were more likely to have hypertension (69.7%), hyperlipidemia (28.9%), ischemic heart disease (22.4%), previous cerebral infract (23.7%) and renal impairment (19.7%). Diabetic infract more frequently occurred in thalamus (11.8%), pons (9.2%) and with cerebral posterior involvement (13.2%). Mortality was higher in diabetic group (P = .046). Conclusions: Diabetic patients had higher risk burden for ischemic stroke with poorer short term hospital outcome than non-diabetic subjects. So control of diabetes and other risk factors along with a strict observation of adult individuals healthy life-style should warrant successful ischemic stroke prevention in our country. J MEDICINE July 2017; 18 (2) : 75-79